Use of powdered egg yolk vs fresh egg yolk for the cryopreservation of ovine semen - Marco-Jiménez, Francisco; Puchades, S.; Mocé, Eva; Viudes-De-Castro, María P.; Vicente, José Salvador; Rodriguez, M. (2017)
Egg yolk is a common additive to sperm cryopreservation diluents. Because of its animal origin, however, it also represents a potential risk of microbiological contamination in the diluent. This potential contamination can be avoided by using powdered egg yolk, instead of fresh egg yolk, as it is pasteurized. This study was conducted to determine ram sperm cryosurvival was affected by the type of egg yolk used (powdered egg yolk or fresh egg yolk) and by yolk concentration (10, 15 or 20%) in the diluent. Microbiological analyses were also performed to quantify the microbiological contamination in the diluents containing the two types of egg yolk. Sperm cryosurvival was determined by motility and morphology analyses after thawing. Motility parameters were assessed using a computer-assisted sperm analysis (CASA) system, and the percentage of sperm with a normal apical ridge was evaluated using a differential interference contrast microscope. No significant differences were observed between diluents in the percentage of sperm with normal apical ridge. However, higher percentages of total motile cells were observed for samples containing powdered egg yolk (69%) compared to samples containing fresh egg yolk (60%). However, sperm in diluents containing fresh egg yolk, exhibited higher values for average-path velocity, straight-line velocity and beat cross frequency and lower values for amplitude of lateral head displacement (p < 0.05), compared to cells in diluents containing powdered egg yolk. Microbiological contamination was similar (< 200 CFU/ml) in both diluents, and no bacterial growth was observed in either, when antibiotics were added. Therefore, powdered egg yolk can be effective used in diluents for the freezing of ram semen. However, the in vivo fertility of sperm frozen in diluents containing powdered egg yolk should be tested, as some motility parameters were different for sperm treated with powdered egg yolk compared to fresh egg yolk.